A correlational study of English language acculturation and language learning motivation in English as a lingua franca learners' context at CELPAD, IIUM - Rozina Muzaffar (Kulliyyah of Education, International Islamic University Malaysia, 2019)
The international students experience English language difficulties which is one of the factors contributing to the lack of acculturation and adjustments affecting the motivational factors of students to reach their maximum potential. This study aimed to investigate correlation between English language acculturation and language learning motivation in English as a lingua franca context at Centre for Languages and Pre-University Academic Development (CELPAD), International Islamic University Malaysia (IIUM). It explores among the respondents' level of acculturation and language learning motivation in the context of English as a lingua franca. Additionally, to see whether the two constructs are related or not and how it influences the international student's language acculturation and language learning motivation. To establish relationship between the two constructs and find out whether the English language acculturation is a significant predictor of language learning motivation. The study population size 271 international students undertaking English language courses at CELPAD, IIUM. The sample was obtained through convenient and stratified sampling technique/method. The sampling was further narrowed down to Level 4, 5, and 6 (students enrolled in CELPAD by their English levels). The questionnaire to be used in the study was validated by conducting pilot study. The questionnaire comprised of 5 items measuring English language acculturation, 19 items measuring self-perception about language ability, and 18 items measuring language learning motivation. Descriptive statistics, Pearson Correlation and Regression Analysis were performed for the data analysis and associations. The results indicate that the level of English language acculturation was moderate with a mean of 3.55. As for language learning motivation, the level was higher with a mean score of 4.127. Moreover, there was a significant positive relationship between English language acculturation and language learning motivation (r = 0.327, p <0.001). Lastly, English language acculturation was statistically significant predictor of language learning motivation with a beta weight of 10.7%, indicating that 90.3% could not be explained by the model. Based on the results, it is recommended that international students should persevere by motivating themselves in English learning and adjust in the Malaysian setup of acquiring English language knowledge to further advance in their academic venture.